Museums of Aragatsotn region as a tourist resource - Margaryan, Varduhi G.; Harutyunyan , Elya H.; Kandyba, Yuriy (Human Geography Journal, 2024)
In the article, we present the museum resources of Aragatsotn region, wanting to raise whether the museum resources of the region are within the scope of tourists’ interests. Museum tourism can be defined as tourists visiting museums in order to get acquainted with certain historical and cultural values and heritage. Museums today are the mainstay of the tourism industry are a part.We have conducted a number of surveys among tourists to record accurate data and raise the issues that concern tourists. Aragatsotn region is distinguished by its natural and man-made recreational resources, among which museums stand out. The public is not aware of many of the museums, so the purpose of this research is to make a cadastral evaluation of the museums and to recommend tourist development routes. Thus, it can be concluded that modern architectural and constructional solutions for museums attract tourists from all over the world, unusual architectural forms arouse the interest of consumers and motivate them to actually visit the museum. In the field of cultural tourism, museum tourism is a special activity of museums known for the production and sale of various tourist products such as creation of exhibitions, organization of internal and external excursions and presence of museum shops. This direction in tourism appeared relatively recently, in the 1970s in the West and in the mid-1990s in Russia. There are many scientific works on museum resources, different authors have referred to museums in different ways, but the goal of all of them is to present the museum as a cultural asset. A new approach to understanding the nature and public purpose of the museum is being developed. The focal point is the person involved in the museum framework rather than the museum itself as an object with its properties and functions. The authors listed above have referred to museums as a tourist resource, presenting an international experience. In the past when visiting a museum there was a norm to be silent in the museum, listen to the tour guide, and only possibly ask a questions in the end after getting permission. All these used to repel the visitors, because they seemed to have appeared in a mold and the rights of the visitor were limited. And now a new culture is emerging, in which it is encouraged to touch museum exhibits, to have an interactive experience, form a clearer picture and develop the imagination. The results may be useful for governmental and local authorities, as well as the private sector, for improving their tourism development policies.